2011
DOI: 10.5588/ijtld.10.0734
|View full text |Cite
|
Sign up to set email alerts
|

Is the delay in diagnosis of pulmonary tuberculosis related to exposure to fluoroquinolones or any antibiotic?

Abstract: Previous treatment with any antibiotic, and not only a FQ, is associated with a delay in TB diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 11 publications
0
16
1
Order By: Relevance
“…A population-based cohort study in Canada between 1997 and 2006 reported that previous treatments with any antibiotics, not only FQ, are associated with delayed TB diagnosis [37]. Use of β-lactams is probably not a confounding factor in the survival analysis, however, because all of the patients in this study received β-lactams on admission.…”
Section: Discussionmentioning
confidence: 96%
“…A population-based cohort study in Canada between 1997 and 2006 reported that previous treatments with any antibiotics, not only FQ, are associated with delayed TB diagnosis [37]. Use of β-lactams is probably not a confounding factor in the survival analysis, however, because all of the patients in this study received β-lactams on admission.…”
Section: Discussionmentioning
confidence: 96%
“…The availability of rapid and accurate diagnostic tests such as the Xpert ® MTB/RIF assay (Cepheid, Sunnyvale, CA, USA), which was endorsed by the WHO in 2010 as part of TB case-finding activities for PLHIV, increases the TB diagnostic yield by 45%, and its use is currently being expanded in Kenya in more health facilities, which would increase TB diagnosis and reduce delays. 2629 To further optimize TB diagnosis among PLHIV, clinicians need to be trained and mentored, laboratory capacity needs to be enhanced with a wider and more efficient network of TB diagnostic testing, diagnostic tests need to be made accessible and affordable and documentation/feedback of results needs to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are consistent with recent reports that have also demonstrated that any antibiotic use, regardless of class, is associated with longer TB diagnostic delays. 14-16 The basis for this delay is poorly understood; however, the delay is likely related to the time spent waiting for a clinical response to the antibiotic. 16 …”
Section: Discussionmentioning
confidence: 99%